Planificación colaborativa de la cadena de suministros del maíz en el Centro Agrícola Servicosecha S.A. - Arroba Macías, Rosa Glenda (2024)
Understanding that the proper functioning of the supply chain promotes the proper management of the actors that make it up, be they suppliers, producers and customers or marketers. The research was developed with the objective of developing the collaborative planning of the Centro Agricola SERVICOSECHA S.A., the methodology to be implemented considers a field and descriptive study in order to know the factors that affect the organization, including its execution in three phases. In the first place, a diagnosis of the supply chain was carried out, to identify how it is integrated. Then, the factors associated with collaborative planning were determined, through the analysis of four variables: planning, replenishment, provisioning and collaborative performance. Finally, a collaborative planning framework was designed, identifying weaknesses and proposing improvement actions to optimize the management of the agricultural center. Regarding the results, they show a medium level of management, control and monitoring of collaborative planning, which affects the full performance of the supply chain, which is why it is concluded that it is a priority to apply actions that favor the interaction of the interested parties. and the formulation of specific strategies aimed at improving and optimizing collaborative planning in the supply chain.